A Study on the Revitalization of Remote Development in Software Industry - Sung Jun, Kim; Hye In, Jung (International Journal of Engineering and Technology, 2018)
Background/Objectives:As public agencies are moving to local relocation, manpower management issues such as dispatching personnel or teleworking are being generated. This point is pointed out by the difficulties of IT service companies such as labor dispatch and burden of system cost. Although it has been specified in the RFP to apply remote development, it is not actually implemented, and it is necessary to supplement the policy for settlement of SW remote developmentMethods/Statistical analysis: I would like to approach a reasonable improvement plan which can derive productivity improvement through remote development by comparative analysis and qualitative case study of representative domestic and overseas cases of remote development.Findings: Firstly, based on the Remote Development Guideline (14.06) published by the Korea Information Society Agency, it is necessary to establish a guideline on the existing guidelines and a notice to utilize them. Second, you should insert a phrase that allows you to refer to the remote development guidelines, such as the subcontracting guidelines. Third, institutional equipment are needed to make the remote development system effective to improve the practices and the SW industry environment.Improvements/Applications: Remote development of the public SW industry is a positive impact.Â